The Genesis of the Turks An Ethno-Linguistic Inquiry into the Prehistory of Central Eurasia - Karatay, Osman, 1971- (Cambridge Scholars Publisher, 2022)
This book suggests a new theory on the origins and Urheimat of the Turks within the context of Central Eurasia and, more properly, the South Urals, by exploring the relations of the Turkic language with the Altaic, Uralic and Indo-European languages and by referring to historical, genetic and archaeological sources.The book shows that the elements that started the making of the Turkic ethno-linguistic entity were also shared by the regions where the later Hungarians would emerge, and that the consolidation of their identity seems to be related to the emergence and rise of the Sintashta culture.